RhCl(TPPTS)3 supported on iota‐carrageenan as recyclable catalysts for Suzuki cross‐coupling. Issue 45 (4th July 2019) - Leviev, Sivan; Wolfson, Adi; Levy‐Ontman, Oshrat
ABSTRACT: A rhodium complex was immobilized for the first time in iota‐carrageenan polysaccharide to render a xerogel catalyst. This new heterogeneous catalyst was successfully used in Suzuki cross‐coupling and was easily separated from the reaction mixture and recycled two times without loss of activity. The rhodium heterogeneous catalyst was characterized by FTIR, SEM‐EDS, and TEM analyses, which demonstrated that the catalyst complex successfully embedded within the polysaccharide and exhibited an unordered, porous structure. Moreover, it was demonstrated that the novel and simple heterogenization procedure, which has been used previously for palladium complexes, is a general route to immobilize transition metal complexes in polysaccharide matrixes. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 136, 48200. Abstract :